Force analysis of tubular fabric during drilling and sampling. Issue 23 (December 2018) - Ding, Zuowei; Yu, Weidong
Based on the principles of kinetics, through analyzing interaction forces among tubular fabric, round pipe and lunar soil simulant during drilling and sampling, it was found that radial elastic properties of tubular fabric, cooperation between tubular fabric and round pipe all influenced the forces. Three different lengths of tubular fabrics were manufactured to verify the analysis. The results testified that the greater the length, the greater the forces at any corresponding time. The relationship between forces and time is linear. The positive correlation relationship in a folded state turned negative and, ultimately, to a fixed value. Compared to theoretical force–time curves, experimental results are bigger and more accurate. Experimental curves demonstrated a creeping phenomenon, which displayed a buckling wave during drilling and sampling. These results offer effective guidance to future research and product design.